Species identification, lifestyles and mitogenomics of the elusive wasp assemblage associated with wild and cultivated olives in the Western Cape - Powell, Chante Melissa (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019